Effect of single and double hemitenotomy on equine deep digital flexor tendon length and strength in experimental load challenges. Issue 7 (18th April 2022) - Zetterström, Sandra M.; Boone, Lindsey H.; Farag, Ramsis; Weimar, Wendy H.; Caldwell, Fred J.
Abstract: Objective: To evaluate a double hemitenotomy (DHT) technique as an alternative to complete deep digital flexor (DDFT) tenotomy. Study design: Experimental ex vivo study. Sample population: Isolated DDFTs ( n  = 30) and cadaveric forelimbs ( n  = 16). Methods: In part 1, 15 isolated DDFT pairs were used. Two hemitenotomies were created in 1 DDFT while the other served as reference. Monotonic tensile load was applied. Tendon lengthening, load reduction, and load at failure were recorded. In part 2, 16 cadaveric forelimb pairs were subjected to DHT followed by complete tenotomy (CT) under monotonic compressive load. Differences between DHT and controls were assessed with Wilcoxon signed rank tests or Friedman tests. Results: In isolated tendons and cadaveric forelimbs, DHT resulted in DDFT lengthening (median, +1.9 mm and + 3.05 mm) and load reduction (median, −16.7 and −11.2 kg). Less lengthening was achieved with DHT compared to CT ( P  = .008). Load reduction did not occur between DHT and CT was observed during compressive testing ( P  = 1). Load reduction following the first hemitenotomy incision was smaller when compared to the second ( P  = .022). Isolated DHT tendons failed at a tensile load of 195 kg, while no intact tendons failed ( P  = .0001). Conclusion: Double hemitenotomy was comparable to CT in load reduction. It reduced tensile strength, but load at failure was similar or exceeded the estimated DDFT load at stance. Clinical significance: Hemitenotomy may be a useful alternative for surgical management of horses with laminitis, but in vivo studies are needed to confirm these findings.